(untitled) (Philological Studies, 2019)
Perception plays an important role in folk texts (puzzle, fairy tale and anecdote). In a puzzle a person who receives a message should reconstruct an answer by changed (transformed) visual characteristics. In a fairy tail the important functions (meeting with antagonist, battle) are formed as visual “pictures”. One of the types of an anecdote (scene) should be reconstructed in a mental view of a listener.